7 - Grand Endeavours and Economic Realities: Managing System-wide Structural Changes to Ugandan Higher Education in the Face of Private Expansion - Salerno, Dr Carlo; Beverwijk, Dr Jasmin (Journal of Higher Education in Africa, 2007)
Uganda’s higher education system has undergone a number of dramatic changes in recent years as part of a three-pronged effort to accommodate rapidly-expanding enrolments, improve the system’s economic efficiency and provide education op- portunities that are better matched to the nation’s labour market needs. This paper examines these key developments in light of the country’s rapidly-expanding pri- vate higher education market. The economic rationale for government regulation of private providers is discussed along with a cost/benefit analysis of three key private higher education related issues that we believe will need to be addressed in the coming years. At the end, we consider how applicable the Ugandan case is to the broader debate and policies associated with private expansion in other developing systems.